If it's not what You are looking for type in the equation solver your own equation and let us solve it.
59y=29(2y+4)
We move all terms to the left:
59y-(29(2y+4))=0
We calculate terms in parentheses: -(29(2y+4)), so:We get rid of parentheses
29(2y+4)
We multiply parentheses
58y+116
Back to the equation:
-(58y+116)
59y-58y-116=0
We add all the numbers together, and all the variables
y-116=0
We move all terms containing y to the left, all other terms to the right
y=116
| 0=x^2+6x+189 | | (2x-7)(3x+1)=388 | | 2w-18w=-64 | | x/2+1/6=x/5 | | 3y+3=-2y-2 | | x/5+9=29 | | 10^2+12^2=c | | 10=3x+40 | | 2x+1=X=1 | | 2x+25+4=x+20 | | 4+12x=35 | | 4/9p^2-25=9 | | t+6t-26+t+8=0 | | 2(11^x-7)-5=113 | | (18x^2+27x+13)=(3x+3) | | -4(-5w+4)-5w=5(w-5)-6 | | X-20=4-3x | | x/6+5=23 | | 0=-16t^2+80t+1600 | | -15n+16=-13n-2 | | 11=1/6x | | x/6-2=28 | | 1/3x-2/3=-3x-4 | | 9+2x-5=3x-3 | | 7w+3+15=60 | | 3/5x-4=14 | | 1/2+y=3/7+2/5 | | -3/u-6=-4 | | 7.6=f+.32 | | x-3.4/7=2.8 | | 4y-3(y+2)=24 | | 2x-23=61 |